ANALISIS BEBAN GEMPA PADA GEDUNG RUMAH SAKIT MENGGUNAKAN METODE STATIK DAN DINAMIK - M. Rifano Anggara; Indra Syahrul Fuad; Ani Firda; Irwandra Septiadi (LATERAL: Jurnal Teknik Sipil, 2025)
RSUD Siti Fatimah Az-Zahra in the province of South Sumatra is the largest regional government hospital in Indonesia. The hospital functions not only as a place of medical care, but also as a complex health service center, which requires a special and well-integrated building structure design. Analysis of the building structure using static equivalent force analysis and dynamic response spectrum analysis methods within the framework of the upper structure with a focus on comparing displacement and base shear. The purpose of this study is to determine the results of displacement and base shear, and to determine the results of comparison of displacement and base shear results using equivalent static and dynamic response spectrum methods. The results of the research conducted using SAP2000 software calculated the displacement that occurred using the equivalent static method shifted by 1.08% in the X direction and by 3.97% in the Y direction, then using the dynamic spectrum response method shifted by 1.41% in the X direction and by 3.56% in the Y direction, while the base shear for the resulting scale factor in the X direction was 1.412 and for the Y direction was 1.119. The displacement comparison results for the equivalent static method in the X direction are smaller than those for the dynamic spectrum response method in the X direction, and for the equivalent static method in the Y direction are larger than those for the dynamic spectrum response method in the Y direction, while for the base shear calculation, the equivalent static method is larger than that for the dynamic spectrum response method, based on the SNI-1726-2019 reference calculated using SAP2000 software, the structure is still in the SAFE category.